DOI: 10.11606/t.17.2020.tde-08022021-141620
|View full text |Cite
|
Sign up to set email alerts
|

Análise de custos da cirurgia de descompressão medular em pacientes com metástases ósseas e associação da sobrevida com as escalas prognósticas de Tokuhashi e Tomita

Abstract: CANDIDO, P. B. M. Cost analysis of spinal cord decompression surgery in patients with bone metastasis and survival association with Tokuhashi and Tomita prognostic scales. 2020. 104 f. Tese (Doutorado em

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
(47 reference statements)
1
1
0
Order By: Relevance
“…Another analysis that also suggests greater severity of our patients is the comparison with the work of Wagner et al 21 In this study, an evaluation of 667 patients operated on in a single oncologic center was performed and a total of 305 patients (45.7%) with some neurological deficit were found, of which only 17 ASIA A (2.5%) and 7 ASIA B (1.1%). 21 Our sample showed 90.2% of patients with some degree of neurological deficit, 5.4% ASIA A and 22.8% ASIA B. Candido et al, 25 who conducted their study in an institution with a similar profile to ours, found 64.07% of patients with some neurological deficit. The statistically significant correlation between Karnofsky's performance scale and ASIA obtained in our analysis, added to these data, could indicate that patients seen in non-specialized SUS quaternary institutions arrive more severely.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Another analysis that also suggests greater severity of our patients is the comparison with the work of Wagner et al 21 In this study, an evaluation of 667 patients operated on in a single oncologic center was performed and a total of 305 patients (45.7%) with some neurological deficit were found, of which only 17 ASIA A (2.5%) and 7 ASIA B (1.1%). 21 Our sample showed 90.2% of patients with some degree of neurological deficit, 5.4% ASIA A and 22.8% ASIA B. Candido et al, 25 who conducted their study in an institution with a similar profile to ours, found 64.07% of patients with some neurological deficit. The statistically significant correlation between Karnofsky's performance scale and ASIA obtained in our analysis, added to these data, could indicate that patients seen in non-specialized SUS quaternary institutions arrive more severely.…”
Section: Discussionsupporting
confidence: 55%
“…3 Metastases of unknown site showed a total of 15 patients (16.3%), consistent with that described in the literature. 25 Although established prevalence data point of the thoracic spine for metastatic implants, 5 we see that this predilection for the thoracic region in our sample (66.3%) is present either in its entirety or in the individual evaluation of the three proposed groups. The prevalence of primary tumors of the spine follows something close to that exposed in the literature (10%) with 12% in our sample.…”
Section: Discussionmentioning
confidence: 52%